Risk of Avascular Necrosis with The Modified Dunn Procedure in SCFE Patients: A Meta-Analysis - Julio J. Jauregui; Nichole M. Shaw; Tristan B. Weir; Sherwin A. Barvarz; Philip K. McClure (MDPI AG, 2022)
In situ stabilization is a widely accepted treatment for slipped capital femoral epiphysis (SCFE) despite risks of avascular necrosis (AVN) and femoroacetabular impingement (FAI). The modified Dunn procedure with surgical hip dislocation attempts to maintain epiphyseal perfusion and allows anatomic epiphyseal repositioning, theoretically reducing AVN and FAI risks. We systematically evaluated the literature, elucidating overall and stability-stratified rates of AVN following the modified Dunn procedure, and revision rates in non-AVN patients. Using Ovid and MEDLINE (PubMed), studies involving the modified Dunn procedure were evaluated for age, stability, preoperative slip (Southwick) angle, ROM at follow-up, outcome metrics, and revisions. Utilizing a random effect model of proportions, we determined overall and stability-stratified AVN rates, and revision rates in patients without AVN.673 patients (688 SCFEs) who underwent modified Dunn procedure were included. Overall AVN rate was 14.3% with a 95% Confidence Interval (CI) of 9.3 to 20.2%. AVN rate in stable slips was 10.9% (95% CI: 6.0 to 17.1%) and 19.9% (95% CI: 12.8% to 28.1%) in unstable slips. Revision rate in non-AVN patients was 13.3% (95% CI: 8.3% to 19.2%). Fixation failures occurred following K-wire or small-caliber (<6.5 mm) screw fixation. Overall mean Harris Hip Score (HHS) was excellent (>90 points). Mean HHS was 98.9 points (range of means: 86 to 99 points) in stable cases, and 90.5 points (range of means: 73 to 98 points) in unstable cases. Patients undergoing modified Dunn procedure had excellent clinical outcomes and low incidences of AVN. Further studies are needed to determine if modified Dunn osteotomy with surgical hip dislocation is a viable alternative to in situ pinning for treatment of severe SCFE.